Thermo Stability Study of Crude Amylase from Bacillus Isolate - Lal, Moti; Verma, Shiv Kumar; Mishra, Vipin; Debnath, Mira (International Journal of Applied Sciences and Biotechnology, 2015)
An amylolytic strain was collected from rotten potato and its activity evaluated. The isolated strain was cultivated for amylase production in shake flasks at 35±2oC and the fermentation pattern was studied. Optimum temperature for maximum enzyme synthesis was observed at 35°C, when initial pH of fermentation medium was adjusted to 5.5. Maximum extracellular amylase activity of 7.9 U/mL and the maximum intracellular activity of 320 U/mL was recorded. Although maximum biomass was present at 12.6 g/L but highest growth rate was observed between 08 to 40h with maximum at 36h. The extracellular amylase present in the broth was partially purified with an overall yield of 44% through purification procedure of ammonium sulphate precipitation. After completed extraction and partial purification and stabilization, the stability of enzyme was observed in a range of temperature and pH between 60°C-90°C and 2-8 pH respectively. Maximum enzyme activity was demonstrated at 90°C, and pH of 5.5 and 6.5. The thermo stability of the amylases of this Bacillus species was comparable to that of amylases from other microbial sources. Int J Appl Sci Biotechnol, Vol 3(3): 427-430